Solvent Effect on Product Distribution in the Aerobic Autoxidation of 2-Ethylhexanal: Critical Role of Polarity - Wang, Zheng; Qin, Yitong; Huang, Huijiang; Li, Guobing; Xu, Yan; Jin, Peng; Peng, Bo; Zhao, Yujun (Frontiers in Chemistry, 2022)
In the aerobic oxidation of aldehydes to acids, how the solvent affect the reaction remains unclear. Herein, the solvent effect in the oxidation of 2-ethylhexanal (2-ETH) to 2-ethylhexanoic acid (2-ETA) was systematically investigated. The vastly different product distributions were observed which could be ascribed to the dominant intermolecular forces. Though strong intermolecular forces in protic solvents limit the oxidation, the optimal 2-ETA yield (96%) was obtained in ipropanol via gradually evaporating the solvent to remove the interactions. Theoretical calculations further revealed that the hydrogen bonds between reactant and protic solvent increase the C-H bond energy (-CHO in 2-ETH). Meanwhile, the hydrogen bonds may improve 2-ETA selectivity by promoting H transfer in the oxidation rearrangement step. Our work discloses the critical role of polarity in determining the reactivity and selectivity of 2-ETH oxidation, and could guide the rational design of more desirable reaction processes with solvent effect.